Rare intraoperative findings during the management of pediatric inguinal pathologies: a decade of experience - Zain, Mostafa; Shehata, Sameh; Elrouby, Ahmed (Frontiers in Pediatrics, 2025)
BackgroundPediatric inguinal surgeries, including procedures for inguinal hernias, undescended testes, and hydroceles, are among the most common surgical interventions in children. While these conditions are well-understood, rare intraoperative findings and anatomical variations can complicate surgical management. This study reviews a decade of experience at a single institution to evaluate the incidence, management, and outcomes of such rare findings.MethodsA retrospective observational study was conducted at a tertiary pediatric surgery center in Egypt, analyzing all inguinal surgeries performed between 2013 and 2022. Patients aged ≤14 years with complete operative records were included. Rare findings were defined as anomalies not typically encountered in standard procedures and were independently reviewed by two surgeons. Data were extracted from surgical logs, operative notes, and electronic records.ResultsAmong 8,756 patients (85.5% male, 14.5% female), rare intraoperative findings were identified in 69 cases (0.8%). These included Amyand's hernia (n = 12), looping vas deferens (n = 34), splenogonadal fusion (n = 2), complete androgen insensitivity syndrome (CAIS, n = 7), congenital unilateral absence of the vas deferens (CUAVD, n = 5), crossed ectopic testes (n = 5), ureteroinguinal hernia (n = 1), Mayer–Rokitansky–Küster–Hauser (MRKH) syndrome (n = 1), and encysted hydrocele (n = 1, female). Most anomalies were identified incidentally, with management tailored to preserve function and minimize complications.ConclusionRare findings in pediatric inguinal surgery, though uncommon (<1%), necessitate surgical adaptability and awareness. Preoperative imaging and laparoscopic techniques enhance detection and management. Training programs should emphasize these anomalies to optimize outcomes.